Is there a relationship between fibroblast growth factor 23 and blood pressure in children with chronic kidney disease - ALPAY, HARİKA (My University, 2022)
BACKGROUND AND AIMS: Chronic kidney disease (CKD) is a complex medical and social problem worldwide due to high prevalence and mortality rates. According to the ESPN/ERA-EDTA, the prevalence of CKD stages 3–5 in children is about 55– 60 pmarp [1]. Moreover, CKD usually causes different severe complications, including pathologic changes in the cardiovascular system, which significantly affect long-term survival. Unlike many complications of CKD, hypertension can be present in the earliest stages of the disease [2]. Nowadays, there has been a scientific and practical interest in Fibroblast growth factor 23 (FGF-23) which is mostly considered as a phosphate-regulating biomarker [3]. There are some speculations that FGF-23 affects blood pressure (BP) in adults due to the impact on the renin-angiotensin-aldosterone system (RAAS) by decreasing calcitriol [4] and the direct effect of FGF-23 on sodium reabsorption, which has been demonstrated in experimental models [5]. Therefore, the aim of our study was to investigate the link between FGF-23 and BP in children with CKD. METHOD: There were 73 children with CKD stages 1–5, mean age was 9.79 ± 0.58 years. BP was determined by 3 times measurement and calculating the mean value. Received results were compared with percentile norms according to age and gender in order to divide patients into two groups: normotensive and hypertensive. FGF-23 was determined in serum by multimatrix ELISA kit (Biomedica Medizinprodukte GmbH, Austria). Statistical analysis was performed using SPSS version 26 (IBM, USA). RESULTS: In the group with normal BP the median of FGF-23 in serum was 1.8 [0.7–3.4] pmol/L. In comparison, in the group with a hypertensive level of BP median indicator of FGF-23 was 7.6 (1.98–18.5) pmol/L (P < .001). The prevalence of elevated FGF-23 in children with high BP predominates 1.6 times [95% confidence interval (95% CI): 1.2–2.1]. It is also noticed that pulse BP positively correlated with FGF-23 level in serum (r = 0.402, P < .001). CONCLUSION: Our findings confirm that FGF-23 is linked to BP in children with CKD what makes us conclude that more careful attention to children with a high level of FGF-23 is needed in relation to hypertension and as a consequence cardiovascular complications. However, more investigations should be done in order to establish a causal relationship.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; TRANSPLANTASYON; Klinik Tıp; Klinik Tıp (MED); ÜROLOJİ VE NEFROLOJİ; TRANSPLANTATION; CLINICAL MEDICINE; Clinical Medicine (MED); UROLOGY & NEPHROLOGY; Üroloji; Transplantasyon; Urology; Transplantation